2021
DOI: 10.3390/nano11092331
|View full text |Cite
|
Sign up to set email alerts
|

Green Afterglow of Undoped SrAl2O4

Abstract: Undoped SrAl2O4 nanocrystals were obtained via solution combustion using urea as fuel. The afterglow properties of undoped SrAl2O4 were investigated. Green afterglow from undoped SrAl2O4 is visible to the human eye when the 325 nm irradiation of a helium–cadmium laser (13 mW) is ceased. The afterglow spectrum of undoped SrAl2O4 is peaked at about 520 nm. From the peak temperature (321 K) of the broad thermoluminescence glow curve, the trap depth of trap levels in undoped SrAl2O4 is estimated to be 0.642 eV usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 48 publications
(109 reference statements)
5
24
0
Order By: Relevance
“…This is the reason why some researchers indexed the peak at around 30.8° as (220). 7,8 Obviously, the diffraction peaks in Fig. 1 match well with the standard XRD diffractograms of monoclinic CaAl 2 O 4 .…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…This is the reason why some researchers indexed the peak at around 30.8° as (220). 7,8 Obviously, the diffraction peaks in Fig. 1 match well with the standard XRD diffractograms of monoclinic CaAl 2 O 4 .…”
Section: Resultssupporting
confidence: 68%
“…Micrometer-sized pores are randomly distributed in the aggregates due to the production of a large amount of gases during the reaction. 3,8,[11][12][13]19,20 Fig. 2(b) shows the SEM micrographs of CaAl 2 O 4 :Dy 3+ to display the channels formed in the aggregates, each scale bar represents 2 mm.…”
Section: Resultsmentioning
confidence: 99%
“…Matsuzawa et al suggested that the band gap of this structure was about 6.52 eV [ 20 ] and considering this wide band gap, impurity‐free SrAl 2 O 4 crystal has no absorption ( λ excitation = 325 nm (3.8 eV), therefore, band‐to‐band emission is not possible in this crystal. [ 21 ] A different case was observed for undoped SrAl 2 O 4 , which is shown in Figure 6 that indicates certain defects are occurring in the host material during heat treatment and caused the emission band at 401 nm under the excitation of UV light (at 325 nm).…”
Section: Resultsmentioning
confidence: 97%
“…Matsuzawa et al suggested that the band gap of this structure was about 6.52 eV [20] and considering this wide band gap, impurity-free SrAl 2 O 4 crystal has no absorption (λ excitation = 325 nm (3.8 eV), therefore, band-to-band emission is not possible in this crystal. [21] A different case was observed for undoped SrAl 2 O 4 , which is…”
Section: Phosphor Powder Synthesismentioning
confidence: 91%
“…This broad emission is ascribed to the existence of defects in the crystal structure because there is no activator in the glass and GC [26]. During the melt process with CO-rich reducing atmosphere, many oxygen vacancies are favorable to be formed in the glass system and preserved in the GC via in-situ precipitation [27], which lead to the generation of traps in the glass and crystal structures. The photoluminescence (PL) profile in the range of 14,285.74-33,333.33 cm −1 of the GC is asymmetric, which can be fitted into three emissions peaking at ~26,429.02 cm −1 (trap 1), ~22,123.89 cm −1 (trap 2), and ~19,685.04 cm −1 (trap 3) (Fig.…”
Section: Photoluminescence Properties Of the Non-doped Gcmentioning
confidence: 99%